The Activating Transcription Factor 3 (Atf3) Homozygous Knockout Mice Exhibit Enhanced Conditioned Fear and Down Regulation of Hippocampal GELSOLIN - Pai, Chia-Sheng; Sharma, Pranao K.; Huang, Hsien-Ting; Loganathan, Srivaishnavi; Lin, Heng; Hsu, Yu-Luan; Phasuk, Sarayut; Liu, Ingrid Y. (Frontiers in Molecular Neuroscience, 2018)
The genetic and molecular basis underlying fear memory formation is a key theme in anxiety disorder research. Because activating transcription factor 3 (ATF3) is induced under stress conditions and is highly expressed in the hippocampus, we hypothesise that ATF3 plays a role in fear memory formation. We used fear conditioning and various other paradigms to test Atf3 knockout mice and study the role of ATF3 in processing fear memory. The results demonstrated that the lack of ATF3 specifically enhanced the expression of fear memory, which was indicated by a higher incidence of the freeze response after fear conditioning, whereas the occurrence of spatial memory including Morris Water Maze and radial arm maze remained unchanged. The enhanced freezing behaviour and normal spatial memory of the Atf3 knockout mice resembles the fear response and numbing symptoms often exhibited by patients affected with posttraumatic stress disorder. Additionally, we determined that after fear conditioning, dendritic spine density was increased, and expression of Gelsolin, the gene encoding a severing protein for actin polymerisation, was down-regulated in the bilateral hippocampi of the Atf3 knockout mice. Taken together, our results suggest that ATF3 may suppress fear memory formation in mice directly or indirectly through mechanisms involving modulation of actin polymerisation.